"How complex and even perverse the real world can be": W.D. Hamilton's early work on social wasps (1964–1968). (August 2017) - Caniglia, Guido
Abstract: William D. Hamilton's name is often connected to important theoretical accomplishments, from the theory of inclusive fitness and kin selection to the so-called Hamilton's rule and the haplodiploidy hypothesis. This article asks: How did Hamilton attempt to test his theory and hypothesis against the complexity of the biological world? The article reconstructs Hamilton's empirical work with social wasps between 1963 and 1968, the years before and after the publication of the groundbreaking "The Genetical Evolution of Social Behavior" in 1964. It points out the centrality of Hamilton's work on wasps and shows how the British scientist attempted to test theories and hypotheses with naturalistic, developmental, and physiological observations as well as, at times, with experimental manipulations. The article offers a new perspective on the history of the scientific understanding of the evolution of social behavior. In contrast to existing narratives, this perspective emphasizes the importance of empirical work—e.g. natural history, physiology, comparative anatomy—which is often obscured by a nearly exclusive focus on theoretical developments in this field. Highlights: The article provides a new perspective on the development of Hamilton's early work on social evolution. The article complements and enriches existing narratives about the field of social evolution. Differently from existing narratives, the article shows the importance of Hamilton's empirical work. The article details for the first time Hamilton's empirical work on social wasps in the 1960s. The article presents new and unreleased material from Hamilton's archive at the British Library.